(untitled) (Medico Legal Update, 2019)
Background/Objectives: Medication errors are one of the most common medical incidents occurring in hospitals and are the major health events. This study aims to perform a meta-analysis of the effects of intervention on the avoidance errors in nurses and to provide basic data for evidence-based nursing practice. Method/Statistical Analysis: CINAHL, PubMed, EMBASE, Ovid, the Cochrane Library and relevant articles published in January 1975 and in February 2018 were searched. Randomized controlled trial and non-randomized controlled trials were included. Risk of Bias and Risk of Bias Assessment tool for Non-randomized Studies were used to evaluate quality of the selected studies. The random effects model was used considering various characteristics of the selected studies to calculate average effect size. Findings: A total of 3538 studies were retrieved from five electronic databases, thirty studies of which were included in this study: five were randomized controlled trials and eight were non-randomized controlled trials. Interventions were medical devices and education intervention. Medical devices intervention was useful to directly reduce nurse medication administration errors (OR=0.64, 95% CI: 0.45 to 0.93. p=.020), and simulation education was effective in improving nurse medication knowledge (SMD=1.06, 95% CI: 0.07 to 2.05, p=.036). Improvements/Applications: The results of this study can be widely used as the bias for the selection of useful moderations to increase safety of patients at nursing sites.